Chemical Sciences for the New Decade. - Ramasami, Ponnadurai (Chemical Sciences for the New Decade ;, 2022)
Chapters collected from "The Virtual Conference on Chemistry and its Applications (VCCA-2021) - Research and Innovations in Chemical Sciences: Paving the Way Forward". This conference was held in August 2021 and organized by the Computational Chemistry Group of the University of Mauritius. These peer-reviewed chapters offer insights into research on fundamental and applied chemistry with interdisciplinary subject matter.